Primary tuberculosis of tonsils: a case report (Faridpur Medical College Journal, 2015)
The occurrence of tuberculosis of the upper respiratory tract including oral cavity has become uncommon. Isolated tuberculosis in the absence of active pulmonary tuberculosis is very rare clinical entity. Here is a report of primary tuberculosis of tonsil, presented with complaints of sore throat.Faridpur Med. Coll. J. 2014;9(1): 58-59